Assimilate and nitrogen remobilization of six-rowed and two-rowed winter barley under drought stress at different nitrogen fertilization. Issue 6 (12th May 2017) - Barati, Vahid; Ghadiri, Hossein
ABSTRACT: Field experiments were conducted to investigate the effects of irrigation regimes and N levels on assimilate remobilization of two barley cultivars (Yousefsix-rowed and Nimrouztwo-rowed ) in 2011 and 2012. There were three levels of water regimes (full irrigation (I100 ), 75% and 50% of I100 : I75 and I50, respectively) in 2011. Rain-fed treatment (I0 ) was included in 2012. Three N levels (0, 60, and 120 kg ha −1 ) were used. Grain yield and assimilate remobilization decreased by severe water stress (I0 ), however, the reduction of them were intensified by N fertilizer application. The N remobilization was negatively affected by N fertilization and water stress. The two-rowed showed higher N remobilization (10.7%) and contribution of N remobilized to N content of grain (5.8%) than the six-rowed. The two-rowed cultivar showed significantly higher assimilate remobilization and grain yield than the six-rowed under I50 (26.3% and 6.5%, respectively) and I0 (48.7% and 17.1%, respectively), while the six-rowed had similar or higher performances in terms of these traits under I100 and I75 . This study showed that optimizing irrigation and N rates (decrease N level with increasing water stress) and selection of the suitable cultivars (Nimrouztwo-rowed ) might increase assimilate remobilization and consequently grain yield under drought stress conditions.